Moisture Retention Characteristics of some Important Soils of Madhya Pradesh in Relation to their Physico-chemical Properties - Sharma, R. B.; Verma, G. P. (Indian Forester, 1972)
Soil moisture characteristics of some important solis of Madhya Pradesh with special reference to regurs were studied. The texture (silt+clay), cation exchange capacity and organic matter content appear to be the dominating factors influencing the moisture retention in these soils. Among tbe clayey soils, the Kamaliakheri series retained the maximum amount of available moistute while Baloda series the least. The amount of available moisture decreased when percentage of clay was >60. Of paddy growing soils, the Panagar soil retained more moisture than Raipur soils. A high amount of exchangeable sodium in an alkali soil seemed to be responsible for the higher available moisture content of an alkali soil as compared to normal soil of tbe same textural group. Statistical analysis of the data indicated that the available moisture in these soils was significantly correlated with silt+clay, cation exchange capacity and organic matter content, while negatively correlated with sand and hydraulic conductivity. The multiple regression equations were also worked out for estimating moisture characteristics.